Hubungan Keterlibatan Ayah dalam Pengasuhan Anak dengan Kemandirian - Desy Ayuningrum (Universitas Lampung, 2019)
The purpose of this study was to determine the relationship of involvement of fathers in parenting with children's independence in Madrasah Ibtidaiyah Pembangunan UIN Jakarta. The independent variable in this study is the involvement of fathers in parenting, and the dependent variable is the independence of children. Data retrieval is done using the scale of father involvement in child care and the independence scale is based on a Likert scale. In this study validity test using Pearson Product Moment Correlation formula and reliability test using Cronbach Alpha with SPSS 22.0 computer program. Based on the results of data analysis, the correlation coefficient between father involvement in parenting and the independence of children was 0.579 with p0,000 0.05. conclusions obtained are Ho rejected and Ha accepted. This shows that there is a significant relationship between the involvement of fathers in the care of children and the independence of children in Ibtidaiyah Pembangunan UIN Jakarta in a positive direction. This means that the higher the involvement of the father in caring for the child, the better the child's independence.Keywords: Father's involvement, independence, early childhoodDOI: http://dx.doi.org/10.23960/jiip.v1i1.18019